Faculty definitions of success in alternative schools and their influences on alternative education - Markham, John Winferd (Kansas State University, 2022)
Alternative education in Kansas is defined as “Alternative education serves students who require or thrive in an environment other than a traditional educational setting” (Alternative School Information for Students and Parents, n.d.). Often, students who are enrolled in alternative education settings are students are defined as “at risk” or students who are simply not successful in a traditional setting. At risk students are deemed at-risk in the opinion of faculty if they fall into the following categories. • Is not working on academic grade level. • Is not meeting the requirements necessary for promotion to the next grade; is failing subjects or courses of study • Is not meeting the requirements necessary for graduation from high school. (e.g., potential dropout) • Has insufficient mastery of skills or is not meeting state standards • Has been retained • Has a high rate of absenteeism • Has repeated suspensions or expulsions from school • Is homeless and/or migrant • Is identified as an English Language Learner • Has social emotional needs that cause a student to be unsuccessful in school (Success | Definition of Success by Oxford Dictionary on Lexico.Com Also Meaning of Success, n.d.) Given the large amount of criteria that can be met within the standards of the definition of at risk, there is a large amount of variety within the population in alternative schools. This variety can lead to wildly different student outcomes when it comes to the curriculum that is presented. Given the fact that the students are placed there to in order to help them become successful (whatever that definition may be to them) The definition of success according to Oxford Languages is simply “the accomplishment of an aim or purpose” (Success | Definition of Success by Oxford Dictionary on Lexico.Com Also Meaning of Success, n.d.). However, different people interpret that definition in vastly different ways. Accomplishment of an aim or purpose can serve many different needs and many different perspectives according to the person whose definition is being used. A success for one person may be a failure for another. The same can be stated for education and the students who make up the populations of high schools across the state. Some students simply view success and education from different perspectives. Many students at a traditional high school setting may only view reaching a post-secondary school as successful. Other students may see graduating high school the culmination of success in their academic career. Other students may simply see passing a class as being a successful endeavor. Definitions of success often drive curriculum and standards that teachers are required to use or standards that they place on their students in their classrooms. Given the wide variety of opinions in how success should or is defined, this can greatly impact the students and their academic futures. Often, curriculum is geared towards students who have a different degree of expectations (and a different definition of success). Other issues that may occur revolve around the students themselves. Simply put, the students’ definition of success can drive what they do in the classroom. Since the definition of success can be wildly individualized in both student and faculty, there isn’t a lot of consistency between the two. Often times students feel successful within the context of a class or a school year, when in fact that faculty isn’t supporting that idea. Ideally, the student would feel that the meeting of each goal would constitute a “success” and want to continue to meet these goals until he or she has achieved their ultimate goal. This continued desire to strive and achieve would allow the student to be able to full fill their potential (whatever that definition is for that student). Another issue is that given the wide variety of students in alternative education, how do their definitions of success, as well as their individual view of potential impact their academic careers? Furthermore, how does the faculty’s definition of success influence the students’ academic expectations and the curriculum they use to teach alternative education students? This study looks to gather an understanding of how faculty define success for alternative education students and how those definitions can influence alternative education and the curriculum that is used for alternative education students.
Keywords: Definitions of success for alternative education students; At-risk; Alternative school; Alternative education; Faculty definitions of success; Alternative school curriculum